PENGUATAN KEMITRAAN ANTARA SERIKAT PEKERJA DAN PENGUSAHA DALAM MENCIPTAKAN LINGKUNGAN KERJA YANG PRODUKTIF - Rizki Fitri Amalia; Firman Freaddy Busroh; Fatria Khairoh (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This community service program aimed to strengthen the partnership between labor unions and employers in creating a productive work environment at PT Pinago Utama Tbk. Harmonious industrial relations play a crucial role in supporting work productivity, organizational stability, and employee welfare. However, differences in understanding regarding the roles of each party, communication mechanisms, and the importance of social dialogue in resolving labor-related issues remain evident. The program was conducted through legal education, case-based learning, Focus Group Discussions (FGD), bipartite dialogue simulations, and evaluation through pre-tests and post-tests. The materials covered harmonious industrial relations, the roles of labor unions and employers, communication and social dialogue, and strategies for building productive partnerships. The results demonstrated a significant improvement in participants’ understanding of industrial relations, stakeholder roles, communication and social dialogue, and conflict resolution through deliberation. In addition to enhancing knowledge, the program also strengthened communication, trust, and cooperation between labor unions and employers. Therefore, this program contributed to the development of a productive, harmonious, and sustainable work environment at PT Pinago Utama Tbk.